Smart detection and classification of fungal disease in rice plants using image processing techniques - Rashed, Akib; Ifraj, Sabista; Toa, Mashfia Zaman (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.